2020
DOI: 10.2139/ssrn.3729969
|View full text |Cite
|
Sign up to set email alerts
|

The Growing Demand for Education in Saudi Arabia: How Effective Is Borrowing Educational Models from the West?

Abstract: The Kingdom of Saudi Arabia (KSA) considers education a top priority, and more emphasis has been placed on this following the 2016 announcement of Saudi Vision 2030. Since then, the country has witnessed several economic and social changes. As a result, the Kingdom has initiated a plan to invest in human capital through education to diversify its economy and increase employment. This includes educational reform with regard to primary and secondary education geared toward preparing students for higher education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This study is situated in regional and global contexts to reveal that the Saudi educational system has not benefited significantly from borrowing educational systems from other countries as these modes do not naturally match student's cognitive development in the country and the Gulf region in general. A study published in 2020 investigates the effectiveness of applying educational models from the West to meet a growing demand for education in Saudi Arabia revealed that the culture of rote learning, and inadequate teacher training were the primary reasons why these systems do not fit naturally within the Gulf region (Mirghani, 2020). The significant issue here is curtailed student's cognitive development In relation to such limitations, Saudi national education system is ineffective to improve learning.…”
Section:  Study Contextmentioning
confidence: 99%
“…This study is situated in regional and global contexts to reveal that the Saudi educational system has not benefited significantly from borrowing educational systems from other countries as these modes do not naturally match student's cognitive development in the country and the Gulf region in general. A study published in 2020 investigates the effectiveness of applying educational models from the West to meet a growing demand for education in Saudi Arabia revealed that the culture of rote learning, and inadequate teacher training were the primary reasons why these systems do not fit naturally within the Gulf region (Mirghani, 2020). The significant issue here is curtailed student's cognitive development In relation to such limitations, Saudi national education system is ineffective to improve learning.…”
Section:  Study Contextmentioning
confidence: 99%